Localization of the questionnaire about sharps disposal at home among diabetes based on knowledge, attitude, and practice theory, and a cross-sectional survey of current conditions - Zan, Haijing; Liu, Tao; Meng, Zhixing; Wang, Jingru (Frontiers in Public Health, 2024)
Background Diabetes Mellitus is a long duration disease, and if a person with diabetes is infected with a blood-borne infectious disease and proper syringe disposal practices are not followed, they run the danger of transmitting the infection to others for a very long period. Whereas fewer research has been done in China on the handing of sharp objects at home. Therefore, there is a need to translate and localize the Knowledge-Attitude-Practice Questionnaire regarding sharp disposal for diabetic patients to assess the current level of patient knowledge, attitudes, and practices and to improve the basis for promoting safe sharps handling practices. Methods This investigation was a cross-sectional study. The Knowledge-Attitude-Practice Questionnaire regarding sharp disposal was localized and debugged and tested for reliability and validity, and then 334 patients were investigated by General Characteristics Questionnaire, Knowledge- Attitude-Practice Questionnaire regarding sharp disposal, and the influencing factors of practice level regarding sharp disposal of patients were analyzed. Results The Cronbach’s α value of the attitude section was 0.864 and the content validity index was 0.923. The knowledge and practice sections are in line with continental language conventions and are easy to understand without any ambiguity. The majority (52%) of the participants had poor knowledge and a neutral attitude toward disposing of sharp objects. Sharps disposal practices among diabetes mellitus patients were poor since about 90% of patients dispose of their used sharps directly into the household waste. Furthermore, we found that level of education, knowledge and attitude were the major predictors of practices regarding sharps disposal among diabetic patients (R2 = 0.573, p < 0.001). Conclusion The Chinese version of the Knowledge-Attitude-Practice Questionnaire regarding sharp disposal has applicability in China. In China, current practice of disposing used sharps is improper. Additionally, the majority of the subjects had low levels of knowledge and attitudes. To raise awareness and encourage diabetic patients to follow appropriate sharps disposal practices, there needs to be ongoing education and a locally tailored safe sharp disposal alternative accessible.